Fundamental aspects of bubble–particle attachment mechanism in flotation separation - Albijanic, Boris; Ozdemir, O.; Hampton, M.; Nguyen, P.; Nguyen, A.; Bradshaw, D. (Elsevier, 2014)
Analysis of bubble–particle mechanism is important for improving our understanding of flotation process. The research presented integrates microflotation experiments, bubble–particle attachment time measurements, and colloid and surface characterization and analysis. The bubble–particle attachment time was inversely related to the flotation recovery and the minimum attachment time matched the maximum flotation recovery, which occurred around mutual isoelectric point for the glass particles and air bubbles. Bubble–particle force measurements, performed with an Atomic Force Microscope (AFM), showed a similar trend. Additionally, the adsorption isotherm of the glass–dodecyl amine hydrochloride (DAH) system indicated that there are the three adsorption regions, and the flotation recovery reached its maximum value in the second region of DAH adsorption on the glass surface. All results obtained in this study showed the important role of colloidal forces affected by surfactant adsorption in bubble–particle attachment.